2019
DOI: 10.1080/21691401.2019.1622554
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cell membrane coated silica nanoparticles loaded with ICG for tumour specific photothermal therapy of osteosarcoma

Abstract: Photothermal therapy (PTT) is a rapidly developing approach for cancer therapy, which has been widely recognized to exert high efficacy as compared to chemotherapy. However, the limited tumour homing property of currently available drug delivery systems (DDSs) is the bottleneck for the efficient delivery of photothermal agents. Here in this study, we surface modified silica nanoparticles (SLN) with the cell membrane (CM) derived from 143B cells to construct a platform (CM/SLN) capable of targeting the homogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…Though the surgery, chemotherapy, and targeted drugs offer symptomatic relief and modest improvement in survival for OS patients, the overall survival rate remains unfavourable . It is widely believed that further research on the underlying mechanisms of OS and the search for novel therapeutic targets are highly desirable to improve the prognosis of OS patients .…”
Section: Discussionmentioning
confidence: 99%
“…Though the surgery, chemotherapy, and targeted drugs offer symptomatic relief and modest improvement in survival for OS patients, the overall survival rate remains unfavourable . It is widely believed that further research on the underlying mechanisms of OS and the search for novel therapeutic targets are highly desirable to improve the prognosis of OS patients .…”
Section: Discussionmentioning
confidence: 99%
“…To date, a number of technologies for cancer treatments have been developed including chemotherapy, radiotherapy, photodynamic therapy, photothermal therapy (PTT), and combination therapy. Among these options, PTT has great potential for effectively treating cancers because of its noninvasive procedure, low toxicity to normal tissues, and high tumour ablation efficiency [1][2][3][4][5][6][7]. Photothermal therapeutic agents that exhibit strong absorbance in the near-infra-red (NIR) region can convert light energy into heat energy to induce hyperthermia (>48 C) and kill tumour cells [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Zhang et al, the silica nanoparticle loaded with photosensitive ICG and coated with osteosarcoma cancer cells showed the better performance of the formulation in both in vivo and in vitro experiments. [81] In a similar study, a silica nanoparticle loaded with photosensitive Chlorins e6 was also observed to show high efficacy in targeting and treatment against gastric cancer both in vivo and in vitro. [82] Combination therapies have always fared better in clinical trials because it helps to control different aspects of the innately complex cancer-ridden body.…”
Section: Photodynamic Therapy Combined With Chemo/immunotherapymentioning
confidence: 86%